Effects of Therapeutic Advice and Patient Education on Anxiety and Satisfaction in Patients Undergoing Cataract Surgery; A Randomized Controlled Trial - Muhammad Ahmed Anwaar, Mahnoor Sajjad, Maria Mustafa, Basit Mahmood, Muhammad Imran Hussain, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anxiety and fear are the most prevalent and most reported negative aspects associated with cataract surgery. However, it is difficult to determine the frequency of patients experiencing it. The data vary depending on the phase of procedure, study group and ophthalmic centre. Proper patient education as well as therapeutic advice may assist in reducing these adverse effects and improving clinical satisfaction and outcomes. Objective: To determine the effects of therapeutic advice and patients’ education on anxiety and satisfaction in patients undergoing cataract surgery. Methods: This was a randomized controlled trial. The study was carried out during the months of January and June of 2021 at Link Medical Centre Lahore. Participants were chosen from list of patients who expressed interest in having cataract surgery. Patients over the age of 17 who were able to understand and communicate, who had not previously had cataract surgery, and who did not suffer from hearing loss were considered suitable. The outcomes used were Calmness scale (1-7), Cooperativeness (1-7), State-Trait Anxiety Inventory (STAI) - Trait Anxiety, low vision quality-of-life questionnaire (LVQoL), Wellbeing (1-9) Results: The results showed that there were 15(65.21%) females in experimental and 16(69.56%) in control group. The mean age and standard deviation were found to be 69.98 (9.7) and 73.14 (14.46) in experimental and control group. The assessment conducted after intervention showed mean and standard deviation respectively in experimental and control group to be as Calmness (1-7), 6.8 (3.7) and 4.8 (2.3), Cooperativeness (1-7), 6.9 (1.2) and 5.3 (3.4), STAI - Trait Anxiety 24.8 (3.69) and 33.9 (2.36), LVQoL, 113.6 (6.8) and 88.6 (4.3), Wellbeing (1-9), 8.4 (2.12) and 7.3 (1.87), while there was significant difference in favour of experimental group (p value < 0.05) in all variables after surgical procedure. Conclusion: The study shows that there were significant effects of therapeutic advice and patient education in favour of intervention group on patients’ anxiety and satisfaction in patients undergoing cataract surgery. More research needs to be done on how well each part works on its own, and more intervention presentations are needed to figure out how well combination therapy works for lowering anxiety. Keywords: Cataract Surgery, Patient Education, Satisfaction, Anxiety, Therapeutic Advice, Nutritional Status